2011
DOI: 10.1007/s13277-011-0263-5
|View full text |Cite
|
Sign up to set email alerts
|

COX-2 and survivin reduction may play a role in berberine-induced apoptosis in human ductal breast epithelial tumor cell line

Abstract: Berberine is an isoquinoline alkaloid that has several pharmacological effects such as antiinflammatory, antimicrobial, apoptosis-inducing and anticancer effects. It has been illustrated that the antiinflammatory effect is mediated by suppressing the nuclear factor-kappa B (NF-κB) that activates expression of some antiinflammatory and antiapoptotic proteins including cyclooxygenase-2(COX-2), inducible nitric oxide synthase (iNOS) and survivin; therefore, berberine may induce apoptosis by reducing antiinflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Previously, non-steroidal anti-inflammatory drugs like ASA and SA were used as an anti-inflammatory and analgesic drugs (67,69,84,70). Findings from this new research and has shown that these drugs can be potentially used to reduce the risk of many cancers in clinical observations (65,66,68,74). It was also identified that these drugs can as well induce apoptosis in various types of cancers (71,73).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, non-steroidal anti-inflammatory drugs like ASA and SA were used as an anti-inflammatory and analgesic drugs (67,69,84,70). Findings from this new research and has shown that these drugs can be potentially used to reduce the risk of many cancers in clinical observations (65,66,68,74). It was also identified that these drugs can as well induce apoptosis in various types of cancers (71,73).…”
Section: Discussionmentioning
confidence: 99%
“…NSAID like ASA and SA are found to be inhibitor of COX enzymes as shown in figure 1, these drugs has been in application for anti-oxidative, anti-microbial as well as antiinflammatory (65,66,67,68,69,70). Some researchers have shown that ASA and SA could be applied as anti-tumour drugs in many cancer cell lines (71,72,73,74).…”
Section: Salicylic Acid As Cox Inhibitormentioning
confidence: 99%
“…Numerous studies have revealed the complex mechanism of COX-2 inducing breast cancer: The overexpression of COX-2 increases PG product, which stimulates cell proliferation leading to the formation of a tumor (22,23); COX-2 overexpression also leads to apoptosis resistance in cancer cells, while the suppression of its activity induces apoptosis (24). Through catalysis, COX-2 overexpression produces more prostaglandin E2 (PGE2) and inhibit the anti-tumor immunity to facilitate the growth of cancer cells (25). Singh and Lucci (26) proved that with COX-2 overexpression in breast cancer, PGE2 inhibits the functions of dendritic cells (DCs), and thus significantly reduces the expression of the co-stimulation molecules B7 and CD40, therefore preventing DC phagocytosis and antigen presence, improving the tumor's immunotolerance and facilitating its escape from immunological surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Nonsteroidal anti-inflammatory drugs (NSAID) such as aspirin, and other NSAIDs were introduced as an antiinflammatory and analgesic drug (Dhillon et al, 2012;El Kebir et al, 2013;Kodela et al, 2013;Yan et al, 2013), while, recent advance shown that it can reduce the risk for colorectal cancer in clinical observations (De LunaBertos et al, 2012;Hsieh et al, 2010;Pazhang et al, 2012;Singh et al, 2010), and induce apoptosis in several cancer (Xiaoxin et al, 2009;Ou et al, 2010;Park et al, 2010). Triptolide is a diterpenoid triepoxide and the major active ingredient of Tripterygium wilfordii Hook.…”
Section: Discussionmentioning
confidence: 99%